Pemanfaatan EcoBrick Sebaga Alternatif Ekonomi Hijau - Alfian Syahbana; Arum Arupi Kusnindar; Azkal Azkal; Regga Regga (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aims to increase the awareness and skills of the Kresnomulyo Village community in utilizing plastic waste into economically valuable products through the Ecobrick technique. Ecobricking is an environmentally friendly solution that can reduce plastic pollution while opening up economic opportunities for the local community. This activity involves a series of events such as socialization, training, and mentoring on the Ecobrick technique and its application to create a sign for Kresnomulyo Village. The sign will serve as a symbol of the village's commitment to environmental conservation and the productive use of plastic waste.This activity is part of the Community Service Program (KKN) of Muhammadiyah University of Pringsewu, which aims to encourage the application of knowledge and technology to solve social issues in the community. During the program, participants received training on how to make Ecobricks and process plastic waste into useful products. Additionally, mentoring was provided to ensure the community can continue these activities independently.The results of this activity show an increase in the community's awareness of environmental issues, particularly plastic pollution. Furthermore, the skills gained by the community in processing plastic waste have added value, with Ecobricks that are not only useful for village needs but also have the potential to be sold, providing extra income for the community. Thus, this program provides dual benefits: protecting the environment and opening up economic opportunities.